In vitro synergistic effects of fluoxetine and paroxetine in combination with amphotericin B against Cryptococcus neoformans - Pereira, Thaís Cristine [UNESP] (2021)
Cryptococcus neoformans is a yeast that mainly affects immunocompromised individuals and causes meningoencephalitis depending on the immune status of the host. The present study aimed to validate the efficacy of selective serotonin reuptake inhibitors, fluoxetine hydrochloride (FLH) and paroxetine hydrochloride (PAH), alone and in combination with amphotericin B (AmB) against C. neoformans. Susceptibility tests were conducted using the broth microdilution method and synergistic effects of combining FLH and PAH with AmB were analyzed using the checkerboard assay. Effects of minimum inhibitory concentration (MIC) and synergistic concentration were evaluated in biofilms by quantifying the biomass, measuring the viability by counting the colony-forming units (CFU/mL) and examining the size of the induced capsules. Cryptococcus neoformans was susceptible to FLH and PAH and the synergistic effect of FLH and PAH in combination with AmB reduced the MIC of AmB by up to 8-fold. The isolated substances and combination with AmB were able to reduce biofilm biomass and biofilm viability. In addition, FLH and PAH alone or in combination with AmB significantly decreased the size of the yeast capsules. Collectively, our results indicate the use of FLH and PAH as a promising prototype for the development of anti-cryptococcal drugs.